DOP13 Immune profiling of adipose tissue in murine models of inflammatory bowel disease (IBD). (25th January 2019) - Letizia, M; Rodriguez Sillke, Y; Schmidt, F; Günther, C; Kunkel, D; Glauben, R; Siegmund, B; Weidinger, C
Abstract: Background: Crohn's disease is characterised by epithelial barrier breaches and a subsequent translocation of bacteria from the intestinal lumen into the adjacent mesenteric fat, inducing fat hyperplasia as well as the recruitment of various immune cells. Nevertheless, the functional role of mesenteric fat in intestinal auto-immunity is unknown and it remains elusive, how intestinal barrier breaches alter the immune cell composition of mesenteric fat. We therefore compared the immunological imprinting occurring upon superficial or transmural intestinal inflammation in mouse models of IBD. Methods: To induce acute or chronic colitis, C57BL/6 mice were either fed 2.5% DSS in their drinking water for 5 days or received 4 cycles of 1.5% DSS for 7 days followed by 7 DSS-free days, respectively. Intestinal epithelial specific caspase-8 (Casp8 ΔIEC ) knockout mice were used as a model for terminal ileitis and compared with wild-type littermates. Immune cells were isolated from mesenteric fat, gonadal fat, mesenteric lymph nodes and intestinal lamina propria and subsequently analysed by mass cytometry using a panel of 36 lineage and functional markers. Results: Our data provide for the first time a comprehensive, comparative immune cell characterisation of lamina propria, mesenteric lymph nodes, mesenteric fat and gonadal fat in DSS-induced colitis or Casp8 ΔIEC -induced ileitis. In all 3 models, immunosuppressive CD64 + CD206 + macrophages were the most abundant myeloid cells found within adipose tissue. Interestingly, in acute DSS, colitis mesenteric fat gained pro-inflammatory characteristics as TNF-α production was induced in CD206 + macrophages, which could not be observed in chronic DSS-induced colitis. In contrast, we observed that CD206 + macrophages infiltrating mesenteric fat of mice with ileitis displayed an up-regulation of anti-inflammatory markers, including CD38 and CD103. Moreover, only the mesenteric fat of Casp8 ΔIEC mice and not DSS colitis models showed infiltration of Ly6G + neutrophils, probably caused by transmural but not superficial inflammation. Finally, adipose tissue of all models showed an enrichment in innate lymphoid cells. Conclusions: Our data suggest, for the first time, a dynamic immune-modulatory function of mesenteric fat in relation to location and development of intestinal inflammation driven by epithelial damage, highlighting a specific anti-inflammatory function of fat tissue upon transmural inflammation. Furthermore, functional assays have to be performed in order to assess a protective function of mesenteric wrapping fat in Crohn's disease.